Resilient health care in global pediatric oncology during the COVID‐19 pandemic. Issue 4 (12th November 2021) - Graetz, Dylan E.; Sniderman, Elizabeth; Villegas, Cesar A.; Kaye, Erica C.; Ragab, Iman; Laptsevich, Aliaksandra; Maliti, Biemba; Naidu, Gita; Huang, Haiying; Gassant, Pascale Y.; Nunes Silva, Luciana; Arce, Daniela; et al.
Abstract : Background: In the face of unprecedented challenges because of coronavirus disease 2019, interdisciplinary pediatric oncology teams have developed strategies to continue providing high‐quality cancer care. This study explored factors contributing to health care resilience as perceived by childhood cancer providers in all resource level settings. Methods: This qualitative study consisted of 19 focus groups conducted in 16 countries in 8 languages. Seven factors have been previously defined as important for resilient health care including: 1) in situ practical experience, 2) system design, 3) exposure to diverse views on the patient's situation, 4) protocols and checklists, 5) teamwork, 6) workarounds, and 7) trade‐offs. Rapid turn‐around analysis focused on these factors. Results: All factors of health care resilience were relevant to groups representing all resource settings. Focus group participants emphasized the importance of teamwork and a flexible and coordinated approach to care. Participants described collaboration within and among institutions, as well as partnerships with governmental, private, and nonprofit organizations. Hierarchies were advantageous to decision‐making and information dissemination. Clinicians were inspired by their patients and explained creative trade‐offs and workarounds used to maintain high‐quality care. Conclusions: Factors previously described as contributing to resilient health care manifested differently in each institution but were described in all resource settings. These insights can guide pediatric oncology teams worldwide as they provide cancer care during the next phases of the pandemic. Understanding these elements of resilience will also help providers respond to inevitable future stressors on health care systems. Abstract : This multinational, multicenter, qualitative study illustrates how pediatric oncology providers used resilient health care strategies, illuminating creative solutions to mitigate impact, many of which may outlast the pandemic.